Structural and conformational insights into SOX2/OCT4-bound enhancer DNA: a computational perspective. Issue 93 (20th September 2016) - Anwar, Muhammad Ayaz; Yesudhas, Dhanusha; Shah, Masaud; Choi, Sangdun
Abstract : The roles of SOX2 and OCT4 are critical in stem cell maintenance either in the context of iPSCs generation or cancer stem cell growth; therefore, it is imperative to study their cooperative binding and SOX2/OCT4-induced DNA conformational switching. Abstract : The potential role of sex determining region Y-box 2 (SOX2) and octamer-binding transcription factor 4 (OCT4) are increasingly discussed in stem cell maintenance either in the context of iPSCs (induced pluripotent stem cells) generation or cancer stem cell growth. These proteins bind to the enhancer and drive the transcription of a multitude of other factors that facilitate stem cell propagation. Here, we elucidated the mechanism of changes in DNA shape and the precise role of the interaction with the proteins, which is necessary to manipulate this ternary complex. Besides bending the DNA, SOX2 drove the DNA into the A-form, whereas OCT4 preferentially shaped DNA into a B-like conformation. SOX2 binding expanded the minor groove with simultaneous shrinkage of the major grove. Greater fluctuation in the DNA and bound proteins was observed after disruption of the protein–protein interaction. Dynamic cross-correlation of DNA atoms was found to be variable, and entropy of DNA atoms from DNA-wild-type-SOX2/OCT4 (DNA WT ) was the lowest among the various complexes. Moreover, essential dynamics-based conformational analysis revealed vivid conformational variation both in DNA alone and in protein bound complexes. Physical parameters such as the diffusion coefficient and dipole moment were also substantially different for DNA from the DNA WT complex. Taken together, our results establish a link between protein–protein and protein–DNA interactions, which will facilitate devising various strategies to modulate this complex in order to regulate the transcription of various proteins.